Beban Pembuktian Tindak Pidana Korupsi Gratifikasi di Indonesia dalam Perspektif Sistem Peradilan Pidana - Pibrezia, Pibrezia; Lasmadi, Sahuri; Hafrida, Hafrida (Wajah Hukum, 2026)
The purpose of this research is to determine and analyze the provisions of the burden of proof system for perpetrators of criminal acts of gratification in the Corruption Law. This is to determine and analyze future regulations regarding the burden of proof system for criminal acts of gratification corruption with the above objectives. The research method used is normative juridical, namely the statute approach, the case approach, and the conceptual approach. The research shows that the Corruption Law has not adopted a reverse burden of proof. As explained in the Law, the burden of proof remains on the defendant, but with the application of a balanced and limited burden of proof. Thus, the defendant must prove ownership of assets related to the public prosecutor's charges, not assets derived from the criminal act of corruption. The public prosecutor still requires evidence of receipt of gratification before starting the proof and proof is limited only to values of more than 10 million which must be proven by the public prosecutor first and then proven the opposite by the defendant. However, for values less than 10 million, the burden of proof remains entirely on the public prosecutor.